Genotypes and Associated Risk Levels of Human Papilloma Virus among Female Patients Attending Rabuor Sub County Hospital, Kisumu - Okwaro, Irene Adhiambo; Onguru, Daniel; Ogolla, Sidney; Odongo, Esther (Mediterranean Journal of Basic and Applied Sciences (MJBAS), 2023)
Background: Human papillomavirus is the main factor in the etiology of cervical cancer, with over 99.7% of cases being associated with high-risk human papillomavirus infection. Although the majority of HPV infections are asymptomatic and self-limiting, persistent HPV infection can result in genital warts, oropharyngeal cancer, and cervical cancer in women, in addition to various anogenital malignancies and other genital warts in both men and women. Method: This was a cross-sectional descriptive study which employed a convenience sampling technique where both qualitative and quantitative methods were used for data collection. A total of 374 participants were enrolled in the study and a semi structured questionnaire was administered to collect socio-demographic, reproductive and sexual history data. Laboratory analysis involved detection of HPV DNA hybrids with a chemiluminescent substrate, Digene Hybrid Capture 2 technology. Descriptive and inferential (logistic regression) analyses at level of significant (a=0.05) were used to summarize the data, and results illustrated using charts and tables. Results: The study findings reported a significant risk level of human papillomavirus among female of age group 40-49 years (AOR; 0.15, 95% CI: 0.03-0.79; p = 0.026). Furthermore, in bivariate logistic regression the circulating HPV genotypes among the respondents was significantly characterized among women of the same age group (95% CI; 0.09-0.7; p = 0.008) as well as in the multivariate regression (AOR = 0.13; 95% CI: 0.02-0.72; p = 0.019). Conclusion: The study thus concluded that there is 23/94 (25.67%) risk of developing cervical cancer due to high risk level HPV (with the presence of low risk level HPV 71/94 (74.33%) known for causing various forms of warts. Therefore, there is need for combined efforts from the Ministry of health and stakeholders to avail and train health care workers on the usage of HPV DNA kits to ensure timely detection of low and high-risk levels HPV. This will ensure timely identification of women at increased risk for the development of cervical cancer, thereby reducing mortality rate.
Keywords: Persistent HPV Infection; Chemiluminescent Substrate; Digene Hybrid Capture 2 Technology; Cervical Cancer Precursors; Circulating HPV Genotypes